A Drosophila cell-free system that senses DNA breaks and triggers phosphorylation signalling. Issue 14 (31st May 2019) - Harpprecht, Lisa; Baldi, Sandro; Schauer, Tamas; Schmidt, Andreas; Bange, Tanja; Robles, Maria S; Kremmer, Elisabeth; Imhof, Axel; Becker, Peter B
Abstract: Preblastoderm Drosophila embryo development is characterized by fast cycles of nuclear divisions. Extracts from these embryos can be used to reconstitute complex chromatin with high efficiency. We now discovered that this chromatin assembly system contains activities that recognize unprotected DNA ends and signal DNA damage through phosphorylation. DNA ends are initially bound by Ku and MRN complexes. Within minutes, the phosphorylation of H2A.V (homologous to γH2A.X) initiates from DNA breaks and spreads over tens of thousands DNA base pairs. The γH2A.V phosphorylation remains tightly associated with the damaged DNA and does not spread to undamaged DNA in the same reaction. This first observation of long-range γH2A.X spreading along damaged chromatin in an in vitro system provides a unique opportunity for mechanistic dissection. Upon further incubation, DNA ends are rendered single-stranded and bound by the RPA complex. Phosphoproteome analyses reveal damage-dependent phosphorylation of numerous DNA-end-associated proteins including Ku70, RPA2, CHRAC16, the exonuclease Rrp1 and the telomer capping complex. Phosphorylation of spindle assembly checkpoint components and of microtubule-associated proteins required for centrosome integrity suggests this cell-free system recapitulates processes involved in the regulated elimination of fatally damaged syncytial nuclei.